ABOUT CREATION AND DEVELOPMENT EDUCATIONAL QUALITY MANAGEMENT SYSTEM - V. Zvonnikov; V. Nefedov (Вестник университета, 2016)
Questions of Educational Quality Management System construction and development are discussed. The experience of the State university management in its construction is resulted. The approach based on a combination of various standards is offered. Standards for the higher education quality assurance in the European space ESG (European Standards and Guidelines) are considered as a perspective direction of Educational Quality Management System development.